Pengamalan Muzik Tradisional Taboh Dalam Budaya Iban Di Sarawak - Noria, Tugang; Anna, Durin (Institute of Borneo Studies, UNIMAS, 2016)
In the Iban society, taboh is one of thier tradisional music. Taboh refers to the tune produced by Iban tradisional music intrument. Taboh has a special place amongst the Iban soceity in Sarawak. This is because taboh is considered as a cultural identity despite relationship between the Iban people or between the Iban people and the gods and supernatural beings. Taboh is not just a tune produced by the musical intruments but also brings symbolic meaning and certain philosophy. Hence, taboh is still a relevant pratice until today. There are few musical intruments played in the taboh Iban music namely gendang, engkerumong, tawak and bebendai. However, tawak is the main musical instrument used to produce taboh amongst the Iban music. Performance of the taboh music vary according to occasion. Occasion namely such as ajat dance and ngajat, a new longhouse was built, blessing of new longhouse, uncloud moon esclipse, healing ritual, and gawai kenyalang festival. Apart from that, is also played for gawai ritual spesifically gawai naku antu pala, also to summon the gods and supernatural beings two week before gawai festival. Summon of gods is to get blessing in the Iban daily life. Taboh is also used as a mesengger for all the Iban longhouse.